ECOTOURISM MANAGEMENT OF THE RAINBOW BRIDGE MANGROVE FOREST IN BANGLAS VILLAGE, TEBING TINGGI DISTRICT, MERANTI ISLANDS REGENCY - Fenty Utari; Dadang Mashur (International Journal Of Humanities, Social Sciences And Business (INJOSS), 2022)
The Rainbow Bridge Mangrove Forest Ecotourism is the only tourist destination in Banglas Village which is managed by BUMDES Banglas Bestari. Mangrove forests have the potential to be managed and developed because mangroves have aesthetic value, therefore cultivating and developing mangroves to be used as tourist destinations in the local area. This study aims to determine how the management of the Rainbow Bridge Mangrove Forest Ecotourism and the obstacles to managing this ecotourism. The theoretical concept used is the management concept of Iwan Nugroho. This study uses a qualitative research method with a descriptive approach. The results of the research found indicate that the management carried out by BUMDES Banglas Bestari has not run optimally where there is no planning document, In its implementation, there are still some things that have not gone well, such as lack of coordination, and control over ecotourism management is still less organized and structured. The inhibiting factors in the management of the rainbow bridge mangrove forest ecotourism  are  limited  funding  sources,  accessibility  and  inadequate facilities and infrastructure, and the imposition of restrictions on community activities (PPKM).